Santos, Jardins da Orla - referência urbana para a comunidade - Banat, Ana Kalassa El; Nunes, Luiz Antonio de Paula (Paisagem e Ambiente, 2002)
This work is part of the Santa Cecília University's Project Portocidade, a reflection about the history of the Santos development and an analysis of your future perspective. The area corresponding to the gardens of Santos border, an arch with about 6 Km of extension and a width of some dozens meters, was object of disputes among the proprietors of the frontier lands to the beach and the public power, during the first decades of the century 20, until that, starting from the thirties, had beginning the construction of lawns on the sand. In 50's the relationship that became established among the beach and the constructions that appeared along the border, and the increase of the occupation of that part of the city, defined the current plan, incorporating the garden definitively to the landscape from Santos. Starting from the sixties the form of occupation of the garden, and your characterization, became dominant in the community's debate, transforming the border's gardens in the most outstanding urban reference of Santos. The alteration of the programs of needs, functions, and the landscape conception, associated to a growing importance given to the individual transport, generated conflicts defining the way as the community sees that equipment.